Theoretical Study of Catalytic Reaction Mechanism of CO with N2O by Cu+ - Chen, Dong-Ping; Gai, Ke; Kong, Chao; Han, Yan-Xia; Hou, Li-Jie; Wu, Bo-Wang (Asian Journal of Chemistry, 2013)
The entire reaction mechanism for the gas-phase CO(C¥v,1S+) + N2O(C¥v,1S) ® N2 (D¥h,1S+g) + CO2(D¥h,1Sg+) catalytic reaction by the bare Cu+ are discussed by the density function theory(DFT). The calculated results explicitly indicated that the reaction exist spin-forbidden phenomenon between the singlet and the triplet potential energy surfaces (PESs). Two crossing points (CP1 and CP2) which play a significant role in this catalytic reaction. The values of the spin-orbit coupling constants are 673.1 cm-1 at CP1 and 284.2 cm-1 at CP2, which indicate that the spin crossing process can occur efficiently due to the large spin-orbit coupling involved. This process made the value of activation energy reduce 108.5 kJ/mol, which are helpful for the reaction on kinetics and thermodynamics.